A global review of determinants of native bee assemblages in urbanised landscapes. Issue 4 (10th February 2022) - Prendergast, Kit S.; Dixon, Kingsley W.; Bateman, Philip W.
Abstract: Loss of natural habitat through land‐use change threatens bees. Urbanisation is a major, increasing form, of habitat loss, and a novel, pervasive form of disturbance known to impact bee diversity and abundance in a variety of often inconsistent ways. We conducted a comprehensive, semi‐quantitative review, involving 215 studies, on responses of bees to urban landscapes, and local and landscape variables proposed to influence bee abundance and diversity. Urban areas tend to be favourable habitat for bees compared with agricultural ones, but compared with natural areas, urban areas often host more abundant populations yet fewer species. Factors associated with urban landscapes, including changes in foraging resources and nesting substrate types and availability, contribute to changes in abundance, species richness, and composition of native bee assemblages. However, the conclusions of studies vary greatly because of the difference in the ecological traits of bees, habitats surveyed, and geographic region, as well as noise in the data resulting from inconsistencies in sampling methodology, and definitions of 'urban' and 'natural'. Identifying what biotic and abiotic features of cityscapes promote or threaten the persistence of urban bee diversity is critical. We provide a comprehensive evaluation of how bees (both in aggregate and according to their ecological guild) have responded to the urban environment, identify gaps in knowledge in urban bee ecology, and make recommendations to advance our understanding of bees in urban environments to promote conservation of diverse bee communities. Abstract : Reviewing 215 studies, factors associated with urban landscapes, including changes in foraging and nesting resources, contribute to changes in abundance, species richness, and composition of native bee assemblages. Urban areas tend to be favourable habitat for bees compared with agricultural ones, but compared with natural areas, urban areas often host more abundant populations yet fewer species. Seven key knowledge gaps are identified, and recommendations on how to advance urban bee conservation.